2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26185
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Experimental Centric Pedagogy in 13 ECE Programs - The View from Students and Instructors

Abstract: Kenneth Connor is a professor in the Department of Electrical, Computer, and Systems Engineering (ECSE) where he teaches courses on electromagnetics, electronics and instrumentation, plasma physics, electric power, and general engineering. His research involves plasma physics, electromagnetics, photonics, biomedical sensors, engineering education, diversity in the engineering workforce, and technology enhanced learning. He learned problem solving from his father (ran a gray iron foundry), his mother (a nurse) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…From the survey results, it seems that the time allotted for use of the portable hands-on hardware is adequate (82%). Similar results have been obtained by thirteen institutions who used the ADB in a collaborative project 17,18 . Table 3 shows the effects of integration of the ADB and Electrical Engineering Practicum on the students in the freshman course.…”
Section: Assessment Resultssupporting
confidence: 84%
“…From the survey results, it seems that the time allotted for use of the portable hands-on hardware is adequate (82%). Similar results have been obtained by thirteen institutions who used the ADB in a collaborative project 17,18 . Table 3 shows the effects of integration of the ADB and Electrical Engineering Practicum on the students in the freshman course.…”
Section: Assessment Resultssupporting
confidence: 84%
“…In-depth analysis identified that satisfaction with use and perceptions of positive outcomes increased as instructor familiarity with the ADBs and experimental pedagogy increased. As noted in previous reports 17,18 , first time student users and novice instructors indicated a need for more introductory materials, videos, and visual aids that would facilitate use.…”
mentioning
confidence: 73%
“…Faculty and students reported an increase in intrinsic motivation, interest in content, and confidence in their ability to learn with 88% of students mentioning that the Analog Discovery Board helped them learn. An increase of students expressing interest in graduate programs and research was also noted [6].…”
Section: Lab-in-a-boxmentioning
confidence: 94%
“…With the increase of current K-12 hands-on constructivist learning, students are entering STEM degree fields expecting to learn via hands-on technology support learning [6]. This mentality along with the increase of STEM enrollment poses a problem for current educators.…”
Section: Introductionmentioning
confidence: 99%